Breakage in Two Points of a Short and Undersized "Affixus" Cephalomedullary Nail in a Very Active Elderly Female: A Case Report and Review of the Literature. (13th September 2018) - Rollo, Giuseppe; Rinonapoli, Giuseppe; Pichierri, Paolo; Bisaccia, Michele; Caraffa, Auro; Meccariello, Luigi
Abstract : Introduction . Trochanteric fractures of the femur are common in elderly individuals with osteoporosis. The use of cephalomedullary nails is increasing, and they are now the most commonly used fixation devices, especially for the treatment of unstable trochanteric fractures. The nail breakage is not the most common complication of intramedullary nailing. Many scientific papers report nail breakage in a specific location: through the lag screw hole, the nail shaft, or the distal locking hole. Materials and Methods . We present a case of an 84-year-old patient treated with modular revision hip arthroplasty due to the breakage in two points of a cephalomedullary nail implanted 3 years earlier for a subtrochanteric fracture. Results . After modular revision hip arthroplasty, the functional results and quality of life have been excellent. Conclusions . As far as we could determine, this appears to be the first case of a breakage of a cephalomedullary nail in two points after nonunion in a very active elderly female.